Error Analysis in Writing Business Letters Among Financial Management Students - Igsi, Christian John Rhod D.; Edianon , Cenverto T.; Castro , Angel Mae B.; Graciano, Lea Charm C.; Saranillo , Kharissa Mae B.; Dacalanio, Mark Aaron A. (CV. Tripe Konsultan, 2025)
The English business writing correspondence is essential for Financial Management (FM) students, impacting their English writing proficiency both in academic and business purposes. This study identified the common errors in the written English business letters of FM students. The researchers employed a descriptive-qualitative method through Error Analysis Theory and Model of Corrective Feedback. Through this method, the researchers gathered data that provided a deeper understanding and analysis of the various writing difficulties encountered by FM students in their business letters. The letters were carefully checked and examined step by step to find and understand the mistakes that students usually make, helping to identify the areas where they often face difficulties and make errors. The results indicated eight types of error, which are sentence structure (21.3%), word choice (18.4%), capitalization (14.7%), preposition (11.8%), pluralization (9.6%), omission of article (8.8%), omission of linking verb (8.1%), and verb tense (7.3%). This implies that FM students are having difficulty in using the correct grammatical rules in writing. It is recommended that the students must be given feedback and great attention to reduce committing errors in writing business correspondence using the target language.